Impact of regional white matter hyperintensities on specific gait function in Alzheimer's disease and mild cognitive impairment. Issue 6 (28th September 2021) - Ogama, Noriko; Endo, Hidetoshi; Satake, Shosuke; Niida, Shumpei; Arai, Hidenori; Sakurai, Takashi
Abstract: Background: Gait disturbance and musculoskeletal changes are evident in persons living with Alzheimer's disease (AD). Because complex gait control requires the integration of neural networks, cerebral small vessel disease (SVD), which is highly prevalent in persons with AD, might have an additional impact on gait disturbance. This study investigated whether white matter hyperintensities (WMH) are more predominantly associated with gait disturbance in persons with AD than in individuals with mild cognitive impairment (MCI) and normal cognition (NC) and further identified the regional impact of WMH on specific gait changes. Methods: This study included 396 subjects (aged 65 to 86 years, 63.9% female) diagnosed with AD ( n = 187), MCI ( n = 118), or NC ( n = 91). WMH, lacunes, perivascular spaces, and cerebral microbleeds were assessed as markers of SVD. The volume of WMH was quantified in each brain lobe (frontal, temporal, occipital, and parietal) and sublobar regions in the basal ganglia and thalamus. Gait function was assessed using an electronic walkway. We investigated the association between regional WMH and gait disturbance in individuals with AD, MCI, and NC, adjusted for classical and musculoskeletal confounders. Results: Among markers of SVD, WMH were most associated with gait disturbance. In AD subjects, periventricular WMH in the frontal and parietal lobes were associated with slow gait speed ( r s = −0.21, P = 0.007 and r s = −0.18, P = 0.019, respectively). These lesions were also associated with changes in stride time, double‐leg support time, and walking angle (all r s > 0.20, P < 0.01). Lesions in the basal ganglia and thalamus were associated with slow gait speed ( r s = −0.16, P = 0.034 and r s = −0.18, P = 0.023, respectively) and greater gait speed variability ( r s = 0.16, P = 0.034 and r s = 0.20, P = 0.010, respectively). MCI subjects showed only associations between sublobar lesions and shorter stride length ( r s = −0.24, P = 0.016) and increased walking angle ( r s = 0.32, P = 0.002). NC subjects did not show associations between WMH and gait parameters. MCI and NC subjects were more affected by muscle weakness than WMH for global gait function ( r s = 0.42, P < 0.001 and r s = 0.23, P = 0.046, respectively). Conclusions: Persons with AD showed a predominant association between WMH and gait disturbance compared with MCI and NC subjects, and regional WMH had a detrimental effect on specific gait changes.